«Liber septem philosophorum». Versione latina L del «Libro dei Sette Savî» (Carte Romanze, 2024)
The essay publishes a critical edition of the Latin L version of the Book of the Seven Sages, belonging to the ancient Italian branch of the legend, together with the versions signed C (northern) and M (Venetian). The edition is based on the three known manuscripts (a Londoner, a Viennese and a Wrocław codex), while the previous text (Mussafia 1867) limited itself to a critical transcription of the Vienna text.
Keywords: Book of the Seven Sages; ancient Italian tradition; Latin version L; textual philology